Tako-tsubo cardiomyopathy presenting with features of left ventricular non-compaction. - Karamitsos, T; Bull, S; Spyrou, N; Neubauer, S; Selvanayagam, J (2008)
Tako-tsubo cardiomyopathy is a poorly understood syndrome. We report a case of a 76-year-old female patient with apical ballooning syndrome and features of left ventricular non-compaction that was followed up by Cardiovascular Magnetic Resonance (CMR) imaging.